Investigation of cast resin transformer manufacturing in AM SGB Sdn Bhd - Valliammai, S.Palaniappan (2012)
This thesis is a research based on the upcoming type of transformer which is a dry type transformer or commonly known as Cast Resin transformer. The study focuses on the manufacturing process of producing Cast Resin transformer as well as the design and quality control. Moreover the advantages using dry type transformer over the other types will be analyzed. On the other hand, this research plays a role on determining solution to overcome limitations faced by the industry while producinghigh voltage coil of dry type transformer. The primary problem involve insulation breakdown. The research will explore several troubleshooting techniques and technologies to diagnose this problem.